A study of Concurrent transaction execution and their problems in Distributed Database System - Singh, Anil Kumar (International Journal of Computer Sciences and Engineering, 2025)
More than one transactions are executing simultaneously is known as concurrent executions. It implies interleaving execution of operations of a transaction. In this paper we will study the benefits of concurrent transactions and problems with concurrent transactions. We will study above with the help of the suitable examples. This paper will help to students and research scholars to understand the concurrent transactions executions